Identifying P100 and N170 as electrophysiological markers for conscious and unconscious processing of emotional facial expressions - Lennard Herzberg; Julia Schräder; Julia Schräder; Han-Gue Jo; Ute Habel; Ute Habel; Lisa Wagels; Lisa Wagels (Frontiers in Behavioral Neuroscience)
IntroductionEveryday life requires correct processing of emotions constantly, partly occurring unconsciously. This study aims to clarify the effect of emotion perception on different event-related potentials (ERP; P100, N170). The P100 and N170 are tested for their suitability as electrophysiological markers in unconscious processing.MethodsUsing a modified backward masking paradigm, 52 healthy participants evaluated emotional facial expressions (happy, sad, or neutral) during EEG recording. While varying primer presentation time (16.7 ms for unconscious; 150 ms for conscious perception), either congruent or incongruent primer / target emotions were displayed.ResultsThe N170 was significantly larger in trials with conscious compared to unconscious primer presentation, while the P100 showed opposite results displaying higher amplitudes in unconscious versus conscious trials. The N170 amplitude was modulated by emotion.DiscussionBoth P100 and N170 were modulated by stimulus presentation time, demonstrating the suitability as potential biomarkers and for systematic research on conscious and unconscious face processing.